Afterword: Nominalizations in syntactic theory - Kornfilt, Jaklin; Whitman, John (Lingua, 2011)
This afterword constructs a working typology of nominalizations, based on but not restricted to the papers collected in this special issue. The typology is based on what we call the Functional Nominalization Thesis (FNT), a version of the model of “mixed projections” proposed in Borsley and Kornfilt (2000) which claims that nominal properties of a nominalization are contributed by a nominal functional projection; above that projection the structure has nominal properties, below it, verbal properties. We argue for four possible levels of nominalization, CP, TP, vP and VP. We show that certain internal syntactic phenomena are characteristic of different levels of nominalization: genitive subjects of nominalization at TP and below, genitive objects of nominalization at vP and below. We suggest that the inventory of categories implicated in nominalization is quite restricted: D, and nominal counterparts of ‘light’ verbal categories. We examine two alternatives to the FNT, the framework of Panagiotidis and Grohmann (2009) and Bresnan's (1997) head-sharing approach, and argue that our treatment is more appropriate under a minimalist approach, as it accommodates the facts within an independently motivated inventory of functional categories, without positing a special type of category limited only to nominalizations. We counter Bresnan's objections against a syntactic derivation of nominalizations by showing that a word's lexical integrity can be successfully violated by “suspended affixation” in syntactically derived nominalizations in Turkish while such integrity has to be respected in lexically derived nominalizations.